Informed trading by foreign institutional investors as a constraint on tunneling: Evidence from China. (12th May 2017) - Zhang, Xiaoxiang; Yang, Xiaotong; Strange, Roger; Zhang, Qiyu
Abstract: Manuscript Type: Empirical Research Question/Issue: This paper investigates how the trading activities of foreign institutional investors (FIIs) affect the tunneling activities of controlling shareholders in an emerging economy (China). Research Findings/Insights: We use an unbalanced panel dataset of 167 FIIs with investments in Chinese real estate firms during the period 2003 to 2011, which gives us 1006 firm‐year observations in total. We find strong support for our hypothesis of an inverted U‐shaped relationship between FII trading turnover and the extent of tunneling by controlling shareholders. Theoretical/Academic Implications: In many emerging economies, the institutional environment for investor protection is weak. Powerful controlling shareholders may take the opportunity to extract private benefits via tunneling activities to the detriment of minority shareholders, and informed minority investors may also take advantage of less well‐informed investors. There are thus multiple principal–principal agency conflicts. FIIs are a particularly important group of informed investors. On the one hand, large‐scale aggressive trading by FIIs should drive stock prices to fundamentals, provide market discipline to management, and thus limit tunneling. On the other hand, FIIs may opt to exploit their private knowledge to gain trading profits at the expense of uninformed investors, and implicitly support tunneling. We highlight these potential effects, and demonstrate empirically an inverted U‐shaped relationship between FII trading turnover and the extent of tunneling. Practitioner/Policy Implications: Tunneling is a serious issue, particularly in emerging economies where the institutional arrangements for minority investor protection are often weak. FII involvement may enhance market discipline, but may also exacerbate the problem, so policymakers need to guard against potential adverse effects. An ownership cap on FII shareholdings is unlikely to be effective, but policymakers might strengthen QFII license revocation policies and issue more licenses to promote competition among FIIs.